(3JHUQI CQHGH GdCdHGH aj cjajI GdfLGI aj GdMQhH ef GdCShGA hfTQ CYdGe GdCYdGe aj GdYOO hGdBdGJ GdeYjfI Ydi dbGA GdCYOGAs - (3eQVj Hf Ydj Hf eQVj GdWQShSj,J (B589 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf hgOGg Edi EjVGM efGgL GdeYGQa ajeG jYjf Ydi GdLgGO s
(3BNQgG (B:s
(3hGf djS ddEfSGf EdG eGSYi hGf SYjg Sha jQi GdMeO ddg QH GdYGdejf s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B203s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs